Engineering unsymmetrically coordinated Cu-S1N3 single atom sites with enhanced oxygen reduction activity - Huishan Shang; Xiangyi Zhou; Juncai Dong; Ang Li; Xu Zhao; Qinghua Liu; Yue Lin; Jiajing Pei; Zhi Li; Zhuoli Jiang; Danni Zhou; Lirong Zheng; et al. (Nature Communications, 2020)
Engineering the coordination environment of single atom catalysts offers to opportunity to optimize electrocatalytic activity. In this work, the authors prepare an unsymmetrical Cu-S1N3 single atom site on porous carbon with high performance in the oxygen reduction reaction.